2021
DOI: 10.1111/wre.12474
|View full text |Cite
|
Sign up to set email alerts
|

Germination biology, distribution and control of the invasive species Eragrostis curvula [Schard. Nees] (African Lovegrass): A global synthesis of current and future management challenges

Abstract: Eragrostis curvula [Schrad. Nees] (African Lovegrass) is an invasive C 4 perennial grass that threatens the multifunctionality of agricultural landscapes in Australia, including agricultural productivity and biodiversity (Firn, 2009;Godfree et al., 2017). It is often described as an undesirable and moderately palatable species that is commonly found on lighter sandy soils along coastal areas within Australia; however, it can also be found further inland if conditions are suitable (Godfree et al., 2017;Roberts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…We found that spread distance was significantly negatively related to frequency of occurrence but not population cover, indicating that the density of range edge populations may not be low. At the local scale, invasive plants may reach high densities shortly after establishment, potentially because of high competitive ability and rapid growth ability (Hamidavi et al, 2021; Roberts et al, 2021). Previous studies on range expanding invasive plants discussed how decreasing population density might explain the patterns they observed, but it is not known whether the densities in edge populations were really low (Bartle et al, 2013; Tabassum & Leishman, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…We found that spread distance was significantly negatively related to frequency of occurrence but not population cover, indicating that the density of range edge populations may not be low. At the local scale, invasive plants may reach high densities shortly after establishment, potentially because of high competitive ability and rapid growth ability (Hamidavi et al, 2021; Roberts et al, 2021). Previous studies on range expanding invasive plants discussed how decreasing population density might explain the patterns they observed, but it is not known whether the densities in edge populations were really low (Bartle et al, 2013; Tabassum & Leishman, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Eragrostis curvula has been suggested to be present in the study area for at least 70 years; as such, it has spread over the area under a changing climate as a result of anthropogenic climate change 47 . As such, this research has chosen to use mean annual temperature data and monthly mean precipitation from 1976 to 2005 as it would best reflect the climatic conditions present in the region during a large time period of its establishment and spread 5 , 47 . For each site, the elevation (m) above sea level (asl) was determined using a one Arc-second resolution digital elevation model based on data collected in February 2000 Gallant et al 38 .…”
Section: Methodsmentioning
confidence: 99%
“…The Eragrostis genus has 300 species worldwide, with 66 present in Australia, 52 native, and 14 considered non-native species 4 . E. curvula was intentionally introduced into Australia as early as 1910 by the Australian Government as part of a larger scheme to introduce soil-stabilising plant species that may also offer a source of feed to grazing livestock 5 , 6 . In Australia, E. curvula has become an undesirable plant species in agricultural and ecological contexts, impacting species diversity, richness, and agricultural productivity 7 , 8 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation